Waste Management and the Formation of Environmental Concern Behavior in the Social Perspective of the Community - Sungkawaningrum, Fatmawati; Istinganah, Alfiatul; Wardani, Anisa Nurul Shanti Kusuma; Azizah, Artika Nurohmatul (Indonesian Journal of Community Services Cel, 2022)
Waste management is still a problem that needs to be resolved. Garbage that is not processed properly will cause things that are harmful to the environment such as pollution to water, soil and air and can cause disease. Therefore, community service activities are needed to increase understanding and awareness so that changes in people's behavior in waste management occur. Community service activities were carried out in Krincing Village, Secang Subdistrict, Magelang Regency at February 2022. With approximately 50 participants. The main activity of community service is in the form of sharing (speech) and discussion followed by questions and answers. Then practice waste management by sorting and selecting which waste still has economic value (price). With this community service activity, understanding and concern for the community is seen to increase by showing enthusiastic and active behavior in waste management practices. In addition, people who have practiced waste management get income from the sale of waste which still has economic value by waste bank (bank sampah).